The Influence of Liqo Tarbawi Activities on the Morals of Ma’had Aly Baitul Hikmah Students - Heri Ariyanto; Nur Hidayah; Sugiyat Sugiyat (PALAPA, 2025)
This study addresses the limited research on the effectiveness of Liqo Tarbawi as a method of character development at the higher education level in pesantren-based institutions, despite growing concerns about moral decline among university students and its implications for future Muslim leadership. The research aims to examine the influence of Liqo Tarbawi activities on the moral character of mahasantri at Ma’had Aly Baitul Hikmah Sukoharjo during the 2024/2025 academic year. Utilizing a quantitative correlational design, data were collected from 87 respondents through total sampling. Instruments included a Likert-scale questionnaire, non-participant observation, and semi-structured interviews. Data were analyzed using descriptive statistics and simple linear regression via SPSS 26.0. The results reveal a positive and statistically significant relationship between participation in Liqo Tarbawi and moral character development, with a correlation coefficient of r = 0.386 and a contribution rate of 14.9%. These findings support Lickona’s (1992) theory of character education and the Islamic tarbiyah framework, which emphasize the role of intensive moral formation through modeling and small-group engagement. The study concludes that Liqo Tarbawi is an effective instrument for cultivating moral character but requires complementary support from familial and institutional cultural environments. Practical implications include the need to strengthen tarbiyah-based curricula, enhance the competencies of murabbi (mentors), and develop community-oriented models of character education. Future research is encouraged to employ longitudinal or mixed-method approaches to capture the deeper processes of internalization.